Hydrological and morphological features and geoecological condition of the territories of the plains area of the Kuma River valley and their significance in the system of civilizational development of the Central Pre‐Caucasus in the 18th–21st centuries - E. G. Mishvelov; Z. V. Ataev; A. I. Kornienko (Юг России: экология, развитие)
Aim. In this work, the main aim was a retrospective analysis of the geo‐ecological state and problems of natural territorial complexes (NTC) of the valley of the plains area of the Kuma River in the context of hydrological and morphological dynamics for the period from the 18th century to the present.Material and Methods. The paper analyses the state of the landscape’s natural components in the region, for which topographic, sectoral and cadastral maps, digital relief model, satellite images were used. Openly available data of ministries, departments, archival and stock materials were used. The degree of anthropogenic transformation of the natural‐territorial complexes was calculated based on the coefficient of ecological stability of landscapes.Result. Using the example of the plains area of the Kuma River for the period of the 18th‐21st centuries, the geo‐ecological features of valley NTC were analysed. Studies have shown that at the present stage meandering remains an important condition for land use in the Kuma River valley in terms of both agricultural land and residential areas. Cartographic schemes of land use of a modelled plot in the valley of the Kuma River were constructed, allowing the assessment of the efficiency of the economic use of the fields of oxbow lakes.Conclusion. For the last two hundred years, valley NTC have remained significant for settlement purposes and related economic activities. The modern meandering belt together with the fields of the older such features create special environment forming conditions for the functioning of the stabilising components of the landscape, floodplain forest being a basic integral factor in the preservation of regional biodiversity. It is recommended that when organising the sustainable use of the land resources of river valleys for the purposes of territorial planning, the regional features of placement of meanders and oxbow lakes be taken into account.